2012
DOI: 10.1182/blood-2012-01-408096
|View full text |Cite
|
Sign up to set email alerts
|

The B subunits of Shiga-like toxins induce regulated VWF secretion in a phospholipase D1–dependent manner

Abstract: AbstractShiga toxin (Stx) causes diarrhea-associated hemolytic uremic syndrome by damaging renal microvascular endothelium. The pentameric B subunits of Stx types 1 and 2 (Stx1B and Stx2B) are sufficient to stimulate acute VWF secretion from endothelial cells, but Stx1B and Stx2B exert distinct effects on Ca2+ and cAMP pathways. Therefore, we investigated other signaling components in StxB-induced VWF exocytosis. Incubation of HUVECs with StxB transiently increased phospholipas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…Shiga toxins induce a profound remodeling of the gene expression repertoire of endothelial cells rather than prompting cell death, provided that vascular cells are subjected to sublethal concentrations of Shiga toxin [199,202]. The net effect is that endothelial cells adopt a prothrombogenic phenotype by expressing increased levels of tissue factor (TF) [203], releasing augmented levels of von Willebrand factor [204,205], and activating platelets [206] via the CXCR4/CXCR7/SDF-1 pathway [202]. In addition, Stx stimulates the expression of adhesion molecules [207] and inflammatory chemokines [208], thereby potentiating the cytotoxity of Stx [209] and promoting the adhesion of leucocytes to endothelial cells, which in turn exacerbate thrombosis and tissue damage.…”
Section: Endothelial Damage: From Stx Cytotoxicity To Thrombotic Micrmentioning
confidence: 99%
“…Shiga toxins induce a profound remodeling of the gene expression repertoire of endothelial cells rather than prompting cell death, provided that vascular cells are subjected to sublethal concentrations of Shiga toxin [199,202]. The net effect is that endothelial cells adopt a prothrombogenic phenotype by expressing increased levels of tissue factor (TF) [203], releasing augmented levels of von Willebrand factor [204,205], and activating platelets [206] via the CXCR4/CXCR7/SDF-1 pathway [202]. In addition, Stx stimulates the expression of adhesion molecules [207] and inflammatory chemokines [208], thereby potentiating the cytotoxity of Stx [209] and promoting the adhesion of leucocytes to endothelial cells, which in turn exacerbate thrombosis and tissue damage.…”
Section: Endothelial Damage: From Stx Cytotoxicity To Thrombotic Micrmentioning
confidence: 99%
“…Phorbol esters, such as phorbol 12‐myristate 13‐acetate (PMA), are potent (non‐physiological) stimulators of VWF secretion that directly activate PKC by mimicking the action of diacylglycerol . Histamine, vascular endothelial growth factor (VEGF) and Shiga toxin 1B (Stx1B) elevate [Ca 2+ ] i in a PLC‐dependent manner, and simultaneously either signal through the Ca 2+ ‐independent PKCδ (VEGF and histamine) or utilize the Ca 2+ ‐dependent PKCα (Stx1B and histamine) . Among its targets are components of the SNARE machinery, the assembly of which is partly regulated through PKC‐dependent phosphorylation events .…”
Section: Stimuli and Signaling Cascadesmentioning
confidence: 99%
“…Both VEGF and histamine activate PKCδ; however, broad‐range PKC inhibition or specific depletion of PKCδ significantly reduced secretory responses after VEGF but not after histamine administration . PKCα is activated by Stx1B as well as by histamine, but is only essential for Stx1B‐induced release; inhibition of PKCα did not block histamine‐induced VWF secretion and, in some studies, even enhanced it . Paradoxically, three independent studies showed that blocking Ca 2+ signaling, which entirely abolishes VWF release induced by both histamine and PKCα‐dependent Stx1B, was not sufficient to fully inhibit VEGF‐induced VWF secretion .…”
Section: Stimuli and Signaling Cascadesmentioning
confidence: 99%
“…One way RalA might operate is through activation of phospholipase D1 (PLD1). PLD1 is required for VWF release (Disse et al, 2009;Huang et al, 2012) and RalA can activate PLD1 in some cell types (Vitale et al, 2005) − although this has not been demonstrated in endothelial cells. Alternatively, in other cells types, RalA can interact with components of the exocyst complex, which then targets vesicles to the plasma membrane (Moskalenko et al, 2002).…”
Section: Modes and Mechanisms Of Exocytosismentioning
confidence: 99%